Transitando el acceso abierto y la ciencia abierta por senderos y estaciones de comunicación de ciencia, tecnología e innovación (La Rivada, 2024)
This article is the result of explorations and reviews carried out in the context of Project 16/H1607-PI “Research data management at UNaM”, which aims, to diagnose the state of the art of open science at UNaM. The project is based on the construction of a central repository that follows the principles of open access to address open science from the management of scientific data that support and validate publications and are generated with public research funds. Here it is pertinent to investigate and expose the regulatory paths that sustains scientific-technological developments in the country and at UNaM. Relevant aspects of national regulations and derived systems are described. Likewise, the study include local procedures which allow the existence and development of platforms that enable the intake and preservation of scientific production in repositories interoperable with other national, regional and international open access and open science networks.